Association of indoor noise level with depression in hotel workers: A multicenter study from 111 China's cities. (25th November 2022) - Li, Li; Liu, Hang; Fan, Lin; Zhang, Nan; Wang, Xinqi; Li, Xu; Han, Xu; Ge, Tanxi; Yao, Xiaoyuan; Pan, Lijun; Su, Liqin; Wang, Xianliang
Abstract: Several studies have elucidated the link between outdoor noise and depression, but the relationship between indoor noise levels and depression symptoms in residential and public places remains unclear. This study was a multicenter observational study with a cross‐sectional design. In 2019, a total of 10 545 indoor noise levels on‐site and 26 018 health data from practitioners were collected from 2402 hotels in 111 cities. Indoor daily noise data levels were detected, and PHQ‐9 questionnaires were used to collect health data. Logistic analysis was used to determine the association between depression score and noise level, negative binomial regression was used to determine potential risks. The geometric mean indoor noise level was 38.9 dB (A), with approximately 40.9% of hotels exceeding the 45 dB value (A). Approximately 19.1% of hotel workers exhibited mild and above depressive symptoms. In addition to functional zoning, geographic location, central air conditioner, decoration status, and other factors had an impact on noise levels ( p < 0.05). Results of logistic and negative binomial regression showed the following: (1) there was significantly positive association between indoor noise and high depression scores above 2 (OR = 1.007, 95% CI: 1.002, 1.012) and (2) some sub‐groups were more susceptible to this effect, especially for the younger female workers working in the first‐tier cities, having higher education level, lower level of income, smoking, and longer working hours. This study confirms an early potential effect of indoor noise on depression. It is recommended to implement evidence‐based measures to control noise sources in hotels.